A novel combination of peripheral nerve blocks for arthroscopic shoulder surgery. Issue 9 (4th August 2017) - Musso, D.; Flohr‐Madsen, S.; Meknas, K.; Wilsgaard, T.; Ytrebø, L. M.; Klaastad, Ø.
Abstract : Background: Interscalene brachial plexus block is currently the gold standard for intra‐ and post‐operative pain management for patients undergoing arthroscopic shoulder surgery. However, it is associated with block related complications, of which effect on the phrenic nerve have been of most interest. Side effects caused by general anesthesia, when this is required, are also a concern. We hypothesized that the combination of superficial cervical plexus block, suprascapular nerve block, and infraclavicular brachial plexus block would provide a good alternative to interscalene block and general anesthesia. Methods: Twenty adult patients scheduled for arthroscopic shoulder surgery received a combination of superficial cervical plexus block (5 ml ropivacaine 0.5%), suprascapular nerve block (4 ml ropivacaine 0.5%), and lateral sagittal infraclavicular block (31 ml ropivacaine 0.75%). The primary aim was to find the proportion of patients who could be operated under light propofol sedation, without the need for opioids or artificial airway. Secondary aims were patients' satisfaction and surgeons' judgment of the operating conditions. Results: Nineteen of twenty patients (95% CI: 85–100) underwent arthroscopic shoulder surgery with light propofol sedation, but without opioids or artificial airway. The excluded patient was not comfortable in the beach chair position and therefore received general anesthesia. All patients were satisfied with the treatment on follow‐up interviews. The surgeons rated the operating conditions as good for all patients. Conclusion: The novel combination of a superficial cervical plexus block, a suprascapular nerve block, and an infraclavicular nerve block provides an alternative anesthetic modality for arthroscopic shoulder surgery.